Adsorption of Rhodamine B on activated carbon obtained from pericarp of rubber fruit in comparison with the commercial activated carbon - Fareeda Hayeeye; Maimoon Sattar; Surajit Tekasakul; Orawan Sirichote (Songklanakarin Journal of Science and Technology (SJST), 2014)
Adsorption of the dye, Rhodamine B, on activated carbon obtained from pericarp of rubber fruit (PrAC) was investigated in comparison with the commercial activated carbon (CAC). Both activated carbons were characterized by scanning electron microscopy (SEM), specific surface area, and pH at point of zero charge (pHpzc). The effects of various experimental parameters such as contact time, dye concentration, amount of activated carbon, pH and temperature were analysed. The adsorption isotherm fitted well into the Langmuir model. By keeping pH constant at 4.0 and varying temperatures at 30, 40, 50, and 60°C, the maximum adsorption were 0.2306, 0.2356, 0.2756, and 0.2981 mmol g-1 for PrAC and 0.8957, 0.9588, 0.9841, and 1.0263 mmol g-1 for CAC, respectively. Study of the effect of temperature dependence of these adsorptions indicated that they were endothermic processes. The adsorption efficiency of Rhodamine B on PrAC is about 80-90%.